"To Rescue the Wretched Ones": Saving Chinese Slave Girls in Republican Xiamen. (January 2014) - White, Chris
<x content-type="archive" xml:space="preserve">Abstract</x> This article examines the Society for the Relief of Chinese Slave Girls, an institution created in Xiamen, Fujian, in 1930 by Xu Chuncao, an influential member in the local Protestant church and Xiamen society. Xu's society established an Asylum to rescue persecuted binü, or "slave girls, " and in total, nearly three hundred girls sought refuge here. Utilizing yearly reports from the Society, this article analyzes the challenges of creating such an organization in Republican Xiamen and the lives of the girls who were housed in the Asylum. The "slave girl" issue in Xiamen was influenced by the mui tsai debates in Hong Kong and Southeast Asia. However, the campaign in Xiamen was unique in that although the Society was not a "church" establishment, it was definitely a Christian institution. Furthermore, the Society in Xiamen was largely removed from the colonial concerns associated with the mui tsai controversy because it was initiated and managed by Chinese.